2009
DOI: 10.1080/01443610903061744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sublingual misoprostol versus intravenous oxytocin in reducing bleeding after caesarean section

Abstract: In this study, 100 singleton pregnant women underwent a caesarean delivery under general anaesthesia and were studied in terms of postpartum bleeding using oxytocin or misoprostol. Patients were randomly divided into two equal groups. One group received two tabs of misoprostol 200 microg sublingually and the second group took intravenous infusion of 20 units of oxytocin at the rate of 10 cc/min immediately after delivery until full contraction of the uterine. The amount of blood loss was lower in misoprostol g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
5
26
0
1
Order By: Relevance
“…Acharya et al [21] compared the effects of 400 μg of oral misoprostol with those of 10 IU of oxytocin; intra-operative blood loss was lower with misoprostol but with increased postoperative shivering. Studies of sublingual misoprostol reported similar results [22,23].…”
Section: Discussionsupporting
confidence: 65%
“…Acharya et al [21] compared the effects of 400 μg of oral misoprostol with those of 10 IU of oxytocin; intra-operative blood loss was lower with misoprostol but with increased postoperative shivering. Studies of sublingual misoprostol reported similar results [22,23].…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, 400 mcg by sublingual route appears to be promising. Two recent trials have confirmed efficacy of sublingual misoprostol in reducing blood loss at cesarean delivery [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual administration of misoprostol has been found to be beneficial in preventing PPH after cesarean delivery [14,15]. A few studies have evaluated efficacy of sublingual misoprostol for prophylaxis of PPH in vaginal deliveries [16][17][18][19][20][21][22]; however, none of them compared the efficacy of this treatment with that of 10 units of intramuscular oxytocin, which is the standard recommended by the WHO [2].…”
Section: Introductionmentioning
confidence: 99%